The Influence of Profitability, Debt Policy, and Liquidity on Firm Value in The Food and Beverage Sector on the Indonesian Stock Exchange From 2018-2021 - Jordhan Baik Simanjuntak; Katrin Monika Silaban; Deby Sintiya Febina Br Sitepu; Sam Gilbert Tarigan; Herlina Novita (Journal of Research in Business, Economics, and Education, 2023)
The food and beverage industry are a manufacturing sector that processes raw materials into finished goods in the form of food and drink products. The Indonesia Stock Exchange (IDX) categorizes this industry under the non-cyclical consumer sector. This study employed a quantitative research method, which, according to Sugiyono (2018), is a research method based on the philosophy of positivism, used to study a specific population and sample. The results revealed that profitability, liquidity, and debt policy simultaneously influence the firm value in the food and beverage sub-sector registered on the Indonesia Stock Exchange for the 2018-2021 period. This conclusion is evidenced by the T-test results. The calculated T-value for profitability's influence on firm value is 4.046, which exceeds the table T-value of 1.998, and the significance level is 0.000, which is less than 0.05. Therefore, it can be concluded that profitability partially has a significant and positive influence on firm value. The T-test results for liquidity's impact on firm value showed a calculated T-value of -0.094, which is less than the table T-value of 1.998, and a significance level of 0.926, which exceeds 0.05. Therefore, it can be inferred that liquidity has a negative impact on firm value. The T-test results for debt policy's impact on firm value showed a calculated T-value of 2.024, which exceeds the table T-value of 1.998, and a significance level of 0.047, which is less than 0.05. Therefore, it can be inferred that debt policy partially has a significant and positive impact on firm value. Based on the calculated F-value of 8.465, which exceeds the table F-value of 2.75, the study accepts the hypothesis that profitability, liquidity, and debt policy simultaneously influence the firm value.